An extreme environment-tolerant anti-icing coating. (23rd November 2022) - Chen, Pengguang; Tian, Shu; Guo, Hongshuang; Wang, Jiancheng; Liu, Xinmeng; Xu, Sijia; Li, Ruiqi; Li, Qingsi; Wen, Chiyu; Yang, Jing; Zhang, Lei
Graphical abstract: Highlights: An anti-icing coating is developed by incorporating PFA-PVP-PDMS and NFs in PDMS. The coating possesses excellent anti-icing and energy-saving deicing performance. The performance only depends on the intrinsic physicochemical property of materials. The amphiphilic anti-icing coating can tolerate various extreme environments. Abstract: Undesired ice accumulation on outdoor infrastructures causes serious economic and safety issues, inducing the urgent demand of anti-icing coatings. However, the outdoor equipment inevitably suffers from various extreme environments, resulting in a challenge for anti-icing coatings to maintain surface structures and material properties that directly affect anti-icing performance. Herein, we develop an anti-icing coating that can tolerate a variety of extreme environments, including ultra-low (-196 ℃) or high temperature (200 ℃), strong acid (pH = 0) or alkali (pH = 14), 168-h ultraviolet (∼6-month sunlight) exposure, and 200-cycle sandpaper grinding. The tough coating can remain intact and maintain deicing performance owing to the incorporation of fluorinated amphiphilic copolymers and photo-thermal nanocarbon fibers in PDMS matrix. The coating can significantly decrease ice nucleation temperature (<-26 ℃), increase icing delay time (∼46-fold delay), and reduce ice adhesion strength (∼17.7 kPa), suggesting both excellent anti-icing and energy-saving deicing performance. This coating is highly promising to outdoor anti-icing applications for universal conditions.